The Effects of Blood Glucose Regulation in Omentin-1 Levels among Diabetic Patients - Arman, Yucel; Kirna, Kerem; Ugurlukisi, Bilal; Kutlu, Orkide; Dikker, Okan; Cil, Eylem Ozgun; Akarsu, Murat; Ozcan, Mustafa; Yuruyen, Gulden; Demir, Pinar; Altun, Ozgur; Ozsenel, Ekmel Burak; Erdem, Mustafa Genco; Sandikci, Riza; Tukek, Tufan (Experimental and Clinical Endocrinology & Diabetes, 2017)
Objectives: Omentin-1, an adipocytokine that increases the insulin sensitivity, has been determined to be reduced in patients with insulin resistance, impaired glucose tolerance, and Type-2 diabetes mellitus. In this study, we have investigated the alterations in Omentin-1 levels with the blood glucose regulation in diabetic patients having poor glycemic control. By this way, we aimed to determine the role of Omentin-1 as a marker in follow-up and monitoring progression of diabetes.Methods: Totally 58 patients with type 2 diabetes mellitus, older than 18 years of age who were having poor glycemic control (HbA1c≥9) were included in this study. In the first visit, all clinical and biochemical parameters of patients were recorded. After baseline evaluation, the patients were advised life style changes, and their medical treatment was determined individually according to the recommendations of the American Diabetes Association guidelines. At the end of the third month patients were re-evaluated. Serum Omentin-1 levels were measured with ELISA.Results: In patients using only oral antidiabetic agents, after exchanging the treatment with insulin, on 3rd month of treatment, there was a significant decrease in serum C-peptide and Omentin-1 levels compared with the initial results (p=0.034, p=0.048, respectively). On the other hand, in patients using insulin treatment from the beginning of the study, there was not any significant alterations in serum C-peptide or Omentin-1 levels compared with the initial results (p>0.05).Conclusions: Serum Omentin-1 levels may change with insulin and metformin treatments in Type-2 diabetic patients. In patients with poor glycemic control, Omentin-1 levels do not change with the regulation of blood glucose levels. A decrease in Omentin-1 and C-peptide levels has been determined after the initiation of insulin therapy. This suggests that, Omentin-1 levels are closely associated with the endogenous insulin reserve and may be used in follow-up of patients.
Keywords: diabetes mellitus; omentin-1; glycemic control